PRAKTIK PENCATATAN BUKU KAS DAN LITERASI KEUANGAN PADA KELOMPOK IBU RUMAH TANGGA DI GOMBAK VILLAGE KUALA LUMPUR MALAYSIA - Nurwahyuni, Nurwahyuni; Fitriani, Fitriani; Hasnidar Syam, Hasnidar Syam (Unit Publikasi dan Jurnal Sekolah Tinggi Ilmu Ekonomi Tri Dharma Nusantara Makassar, 2023)
Household finances are not an easy thing, you need to manage household finances correctly so that all the needs of various family members can be met. Managing family finances well, managing carefully how expenses match the income earned, is one of the keys to family success. And you need to understand that managing household finances is not only an individual's responsibility, but husbands and wives have the same important role and responsibility for managing finances in their household. However, in most conditions in people's lives, the wife plays the role of treasurer or minister of household finance. This community service activity program collaborates with partners. This form of service is carried out through the promotion of financial literacy and the practice of recording shopping books for housewives. This activity aims to increase and foster financial literacy knowledge for housewives so they are able to be wiser and manage household income and expenses, in order to meet their daily needs. The results achieved can be seen from the positive and enthusiastic responses from the participants. Participants were communicative with question and answer sessions and sharing during the service activity process. Activities like this are very beneficial for partners, especially housewives, some of whom work as cleaners, thereby increasing their knowledge in recording household finances. The service teamhopes that activities like this can continue with different themes and the creation of basic accounting consulting services and simple bookkeeping of household finances